Some general properties of a fractional Sumudu transform in the class of Boehmians - Shrideh K. Qasem Al-Omari; Praveen Agarwal (Kuwait Journal of Science)
In literature, there are several works on the theory and applications of integraltransforms of Boehmian spaces, but fractional integral transforms of Boehmians havenot yet been reported. In this paper, we investigate a fractional Sumudu transform ofan arbitrary order on some space of integrable Boehmians. The fractional Sumudutransform of an integrable Boehmian is well-defined, linear and sequentially completein the space of continuous functions. Two types of convergence are also discussed indetails.